Catalyst free carbon nitride nanostructures prepared by rf-PECVD technique on hydrogenated amorphous carbon template - Khanis, N.H.; Ritikos, R.; Othman, M.; Abdul Rashid, N.M.; Ab. Gani, S.M.; Rahman, Saadah Abdul (Elsevier, 2013)
Catalyst free nanostructured carbon nitride thin films were synthesized by radio-frequency plasma enhanced chemical vapour deposition (rf-PECVD) on pre-deposited hydrogenated amorphous carbon layer (C:H). The effects of the morphological and structural properties of the pre-deposited C:H underlayer on the formation and the corresponding carbon nitride nanostructures (ns:CN x) were studied. The C:H underlayers were produced from pure methane plasma while the carbon nitride nanostructure were formed from a mixture of methane and nitrogen. The effects of varying the applied rf powers on the morphological and structural characteristics of the C:H underlayer and the resulting ns:CNx films were determined. The C:H underlayers were studied using Fourier Transform Infrared (FTIR) Spectroscopy and Atomic Force Microscopy (AFM) while Auger Electron Spectroscopy, FTIR Spectroscopy, and Field Emission Scanning Electron Microscopy (FESEM) were used to study the carbon nitride nanostructures product. The results showed that the change in the surface morphology of the C:H has significant influence on the features of the resulting carbon nitride nanostructures. Â© 2013 Elsevier B.V. All rights reserved.